(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A political party “Young Khiva people”, whose goal was the political, economic and cultural rise of the country through democratic reforms in the territory of the Khanate, relied on the alliance of the Red Army troops and the Communists of Turkestan to overthrow the Khanate of Khiva.